Optimization of Preparation Process of Antioxidant Peptides from Golden Pompano (Trachinotus ovatus) Skin by Response Surface Method and Its Composition Analysis - Ziying SU; Xuli LU; Yaping DAI; Yupo CAO; Long ZHENG; Jihua LI; Yi ZHANG (Shipin gongye ke-ji)
In order to promote the comprehensive utilization of the resource of golden pompano skin, this study investigated the optimal preparation process of its antioxidant peptides using golden pompano skin as raw material. Taking hydrolysis degree and DPPH free radical scavenging rate as inspection indexes, the enzymatic hydrolysis conditions of golden pompano skin, including enzyme type, time, enzyme amount, temperature and pH were optimized on the basis of single factor experiment combined with response surface methodology. Therefore, the optimal enzymatic hydrolysis conditions of antioxidant peptides from golden pompano skin were obtained, and the molecular weight distribution and amino acid composition of enzymolysis product were further determined. The results showed that the optimal enzyme for the preparation of antioxidant peptides from the golden pompano skin was alkaline protease, and the optimal enzymatic hydrolysis conditions were: Enzymolysis temperature 52.3 ℃, pH10.0, time 8.4 h and enzyme amount 15409 U/g. The DPPH free radical scavenging rate of the enzymolysis product obtained under the optimal enzymatic hydrolysis conditions was 81.59%±2.96%. The molecular weight of the enzymolysis product was mainly distributed below 3000 Da, accounting for 79.20%. Besides, 17 kinds of amino acids were detected in the enzymolysis product, of which glycine was the main amino acid and hydrophobic amino acids accounted for 35.28%. The results of this study provide a theoretical basis for the high-value utilization of golden pompano skin and the screening of antioxidant peptides.